Ultrasound-Guided Single-Penetration Dual-Injection Block for Leg and Foot Surgery: A Prospective, Randomized, Double-blind Study. Issue 1 (1st January 2014) - Børglum, Jens; Johansen, Karina; Christensen, Margrethe D.; Lenz, Katja; Bendtsen, Thomas F.; Tanggaard, Katrine; Christensen, Anders F.; Moriggl, Bernhard; Jensen, Kenneth
Abstract : Background and Objectives: We describe a new approach to blocking the sciatic and saphenous nerves in the proximal thigh (level of the lesser trochanter or immediately below) using a single-penetration dual-injection (SPEDI) technique. The popliteal-sciatic approach necessitates repositioning of the leg exposing the popliteal fossa and an extra injection for the saphenous nerve (SAN) block at the midthigh level. We introduce an alternative, effective, and possibly faster method. Methods: Sixty patients undergoing leg and foot surgery under general anesthesia were included. We deposited 15 mL of ropivacaine 0.75% around the sciatic nerve (SCN) and 5 mL of ropivacaine 0.75% at the SAN. Patients were randomized to the popliteal-sciatic/saphenous technique or the SPEDI technique. The primary outcome measure was performance time. Positioning time, pain assessment, nausea in the postanesthesia care unit, sufentanil demand, dermatomal anesthesia, and degree of motor blockade were also recorded. Results: Performance time was significantly faster with the SPEDI technique (median time, 110 seconds [range, 57–315 seconds] vs 246 seconds [range, 163–472 seconds]; P < 0.0001). Positioning time was significantly shorter with the SPEDI technique ( P < 0.0001). No other statistically significant differences were recorded. Conclusions: The SPEDI block resulted in significantly faster performance time and reduced positioning time with statistically equal efficacy in relation to pain assessment, nausea, sufentanil demand, dermatomal anesthesia, and motor blockade. The SPEDI block is statistically an equally effective alternative to the traditional popliteal-sciatic/saphenous block combination for leg and foot surgery, but it is faster, requires only 1 skin penetration, and does not require repositioning of the leg.